Gamification as a strategy to use b1 vocabulary in 2ND – 3 RD Bachillerato General Unificado At Unidad Educativa Jacinto Collahuazo - Hernández Mediavilla, Alexis David (2025)
To apply gamification principles for vocabulary usage in 2nd and 3rd BT and BGU students at Unidad Educativa Jacinto Collahuazo.